Two-parameter fracture model for cortical bone - Sabrina Vantadori; Andrea Carpinteri; Giovanni Fortese; Camilla Ronchei; Daniela Scorza; Filippo Berto (Fracture and Structural Integrity)
The analysis of the bone fracture behaviour is fundamental for prevention, diagnosis and treatment of traumas. In the present paper, an experimental analysis of the fracture behaviour of a bovine femoral cortical bone is carried out, where specimens are extracted from a diaphysis. Fracture toughness is computed by employing a two-parameter fracture model originally proposed for concrete. In order to take into account the possibility of crack deflection (kinked crack) due to osteons orientation, a modified version of such a model is here discussed. The fracture toughness results are then compared with those reported in the literature, related to a femur of an 18-month-old bovine.